Four-hour voiding observation with provocation test reveals significant abnormalities of bladder function in newborns with spinal dysraphism. Issue 4 (August 2020) - Wide, Peter; Duchén, Karel; Mattsson, Sven; Glad Mattsson, Gunilla
Summary: Introduction: Four-hour voiding observation with provocation test (VOP) using a scale, a damp detector and ultrasound for determination of residuals, is an easily performed non-invasive method for the evaluation of bladder function in newborns. Neonatal bladder function evaluated with VOP has been described for healthy newborns (HN) but not for children with spinal dysraphism (SD), for whom early bladder evaluation is essential for decisions regarding Clean Intermittent Catheterization and follow-up. The aim of the present study was to describe voiding observation with provocation test in newborns with spinal dysraphism and compare with corresponding data for healthy newborns. Methods and materials: At a tertiary hospital, a 4 h voiding observation with provocation (VOP) was performed in 50 neonates (22 girls, 28 boys) with spinal dysraphism (37 open SD, 13 closed SD) consecutively evaluated for possible neurogenic bladder-sphincter dysfunction (1998–2019). All newborns with open SD and 4/13 with closed SD had been through postnatal neurosurgery before the test. Mean age was 10 days. Voiding observation was performed during 4 h with visual observation the fourth hour recording behavior and urinary flow (e.g. stream, dribbling). Finally, bladder provocations (e.g. suprapubic compression) were performed, and any leakage was noted. Findings were compared to those of 50 healthy newborns (HN) earlier published (Gladh et al., 2002). There were no significant differences in background data such as gender, age or diuresis between newborns with SD and HN. Results and discussion: Voiding observation with provocation test of children with SD revealed significant differences compared to HN see summary table. Some children with SD had frequent small voids/leakages and low bladder volumes while three had no voiding and high volumes. Leakage during bladder provocation test and not voiding with a stream was not seen in HN but were common in newborns with SD (69% resp. 74%) (p < 0.01). A child with these findings should thus be investigated further. Identifying children needing Clean Intermittent Catheterization is important as well as being able to postpone or refrain from invasive urodynamic studies if not strongly indicated. VOP may give valuable information for these judgements. Conclusion: Newborns with spinal dysraphism differ from healthy newborns in many aspects of bladder function. Bladder function varies between newborns with closed and open spinal dysraphism. Many newborns with spinal dysraphism leak at bladder provocation and void without a stream but healthy newborns do not. Early determination of post-void residuals is mandatory in children with spinal dysraphism and non-invasive VOP gives this information in a standardized way, also adding information on frequency, voiding with a stream and leakage at provocation. Summary Table Results of VOP for newborns with spinal dysraphism and healthy newborns, volumes group median and range (ml). Data for visual observation of voiding and for provocation test missing for four and two children respectively. Summary Table Newborns with SD Healthy Newborns All SD SD vs HN Open SD Closed SD HN & Number of children 50 37 13 50 Voiding frequency 5.6 (0–14) <0.001¤ 6.1 (0–14) b 4.6 (2–8) a 4.0 (2–7) <0.001 Max voided volume 18 (0–67) <0.001¤ 15 (0–42) b 31 (11–67) a 35 (15–77) <0.001 Median voided volume 8.3 (0–36) <0.001¤ 6.5 (0–22) b 19 (5–36) a 23 (10–49) <0.001 Median residual volume 13 (0–80 <0.01¤ 17 (0–80) b 6.0 (0–28) a 7.5 (0–34) <0.005 Minimum residual volume 1.0 (0–80) <0.01¤ 5.0 (0–80) b 1.0 (0–7) a 0.0 (0–26) <0.01 Voiding with stream 12/46 (26%) <0.01 € 5/37 (14%) c, d 7/13 (54%) c 50/50 (100%) Leakage at provocation 33/48 (69%) <0.01 € 30/37 (81%) c, d 2/11 (18%) c 0/50 (0%) ¤ = Mann Whitney; & = Kruskal–Wallis between open SD, closed SD and HN; € = Chi 2 test. a Significant difference compared to open SD, p < 0.05, Mann Whitney. b Significant difference compared to HN, p < 0.01, Mann Whitney. c Significant difference compared to HN, p < 0.05, Chi-square test, Fisher's Exact Test. d Significant difference compared to closed SD, p < 0.05, Chi-square test, Fisher's Exact Test.